A systematic approach to diverse, lead-like scaffolds from α, α-disubstituted amino acids. Issue 56 (26th May 2015) - Foley, Daniel J.; Doveston, Richard G.; Churcher, Ian; Nelson, Adam; Marsden, Stephen P.
Abstract : A strategy for the efficient lead-oriented synthesis of novel molecular scaffolds is demonstrated. Twenty two scaffolds were prepared from four quaternary α-amino acid building blocks in only 49 synthetic operations, using six connective reactions. The ability of each scaffold to specifically target leadlike chemical space was demonstrated computationally. Abstract : A powerful strategy for the efficient lead-oriented synthesis of novel molecular scaffolds is demonstrated. Twenty two scaffolds were prepared from just four α-amino acid-derived building blocks and a toolkit of six connective reactions. Importantly, each individual scaffold has the ability to specifically target lead-like chemical space.